PENGARUH PEMBERIAN MADU DAN KUNYIT TERHADAP PENURUNAN NYERI MENSTRUASI (DYSMENORRHEA) PADA REMAJA RW 05 DESA WINDUNEGARA - Alfia Nur Karimah; Syamsul Anwar (MNJ (Mahakam Nursing Journal), 2023)
Menstrual pain is part of the clynical process that occurs in women. So this study aims to determine the effect of drinking honey and turmeric on menstrual pain (dysmenorrhea). The research design of this study was a quasi-experiment with one grup pretest and posttest. The research sample consisted of 18 respondents consisting of young women Rw 05 Windunegara Village. The sampling technique used Total sampling. Data analysis used descriptive statistics and non-parametric statistical tests using the Wilcoxon test with a significance level of Asym.Sig (2-tailed)<0.05. Drinks of honey and turmeric was given as much as 120-200 mL 3 times a day for 2 days. Pain intensity was measured using Numeric Rating Scale (NRS) before and after administration of honey and turmeric drinks. The length of time between pretest and posttest was according to the respondent’s menstrual cycle. From the statistical results of the study, the NRS values before and after drinking turmeric honey were 5,78 and 0,56. The test results obtained a significant difference Asymp Sig (2-tailed) = 0.000. the results of this study showed a significant difference betwen drinking honey and turmeric in reducing menstrual pain (dysmenorrhea). Suggestions : This Research can be used as input for utilizing herbal drinks to reduce menstrual pain.